The impact of contracting out on the costs of refuse collection services: the case of Ireland - Reeves, Eoin; Barrow, Michael (Economic & Social Studies, 2000)
This paper examines the impact of contracting out on the costs incurred by local authorities in providing refuse collection services. Using original survey data for the Republic of Ireland, three methods of estimating the impact of tendering are adopted. Crude comparisons of costs before and after tendering and the costs of local authorities versus private contractors indicate that tendering can yield savings of between 34 and 45 per cent. Using multivariate regression analysis to enable us to control for service characteristics confirms cost savings of around 45 per cent. The bulk of these cost savings are attributed to real efficiency gains as a result of contracting out.
Keywords: Contracting out; Local government; Ireland; Tendering; Refuse collection services